2017
DOI: 10.1073/pnas.1617523114
|View full text |Cite
|
Sign up to set email alerts
|

Helical structure, stability, and dynamics in human apolipoprotein E3 and E4 by hydrogen exchange and mass spectrometry

Abstract: Apolipoprotein E (apoE) plays a critical role in cholesterol transport in both peripheral circulation and brain. Human apoE is a polymorphic 299-residue protein in which the less common E4 isoform differs from the major E3 isoform only by a C112R substitution. ApoE4 interacts with lipoprotein particles and with the amyloid-β peptide, and it is associated with increased incidence of cardiovascular and Alzheimer's disease. To understand the structural basis for the differences between apoE3 and E4 functionality,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
35
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 56 publications
5
35
0
Order By: Relevance
“…Both our HDX study and those of Chetty et al (22) support the validity of the NMR structure of the apoE3 monomeric mutant as determined by Chen et al (10). Any differences in comparing wild-type apoE3 and apoE4 between our data and those of Chetty et al (22) are likely due to different sample handling and data analysis methods.…”
Section: Resultssupporting
confidence: 81%
“…Both our HDX study and those of Chetty et al (22) support the validity of the NMR structure of the apoE3 monomeric mutant as determined by Chen et al (10). Any differences in comparing wild-type apoE3 and apoE4 between our data and those of Chetty et al (22) are likely due to different sample handling and data analysis methods.…”
Section: Resultssupporting
confidence: 81%
“…Nuclear magnetic resonance [7] and hydrogen‐deuterium exchange mass spectrometry studies [10–12] also showed that Arg112 interacts with Lys95, leading to a marked change in protein folding. On the basis of these and other structural studies, phthalazinone derivatives known as “correctors” were designed in an attempt to inhibit this interaction and convert apoE4 to an E3‐like configuration [13].…”
Section: Introductionmentioning
confidence: 99%
“…A recent study of intact tetrameric apoE3 by HDX-MS [43] found the helix bundle organization to be broadly similar to that of the monomeric apoE3 studied by NMR. These authors noted a stable NT domain helix bundle and a long CT helix with markedly reduced stability for apoE3.…”
Section: Discussionmentioning
confidence: 88%
“…Interestingly, other researchers also reported that 27 out 43 peptides generated from the N-terminal segment (residues 1-191) of full length apoE3 elicited EX1/EX2 kinetics [43], indicating high occurrence of mixed HDX kinetics. Due to the challenges fitting mixed EX1/EX2 HDX kinetic mechanism, we classified (Figure S2) 15 peptides into two groups based on their experimentally observed HDX pattern: those that exhibit EX1/EX2 mixed HDX profile and those that exhibit binomial HDX profile (Table 1).…”
Section: Discussionmentioning
confidence: 99%